The Effect of Work-Life Balance and Organizational Commitment on Employee Performance with Job Satisfaction as a Mediator : Study at the Central Java High Court - Kartika Novita Sari; Suhana Suhana (Journal of Management and Social Sciences, 2026)
Employee performance is a crucial factor in supporting organizational effectiveness and the achievement of institutional goals. This study aims to analyze the influence of Work-Life Balance and Organizational Commitment on Employee Performance, with Job Satisfaction as a mediating variable at the Central Java High Court. A quantitative approach with a survey method was employed. The population comprised all non-judge Civil Servants (ASN) at the Central Java High Court, with 94 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed through Structural Equation Modeling-Partial Least Squares (SEM-PLS) using SmartPLS 4.0. The results indicate that Work-Life Balance has no significant direct effect on Employee Performance, whereas Organizational Commitment has a positive and significant effect. Furthermore, Work-Life Balance has a positive and significant effect on Job Satisfaction, as does Organizational Commitment. Job Satisfaction also has a positive and significant effect on Employee Performance. The findings further demonstrate that Job Satisfaction significantly mediates the relationship between Work-Life Balance and Employee Performance, as well as the relationship between Organizational Commitment and Employee Performance. These findings suggest that improving employee performance at the Central Java High Court can be achieved more effectively by strengthening organizational commitment and enhancing job satisfaction. Although Work-Life Balance does not directly influence employee performance, maintaining a healthy balance between professional and personal life remains important because it can increase job satisfaction, which subsequently contributes to improved employee performance and organizational effectiveness.